Optimization of English Ability for Grade 10 Students at At-Tajdid Blora High School Through Speak It, Love It, Ace It Method - Helmi Gunawan; Hertnacahyani, Eva; Wahyusari, Retno; Suryanto, Hendri (Universitas Nusantara PGRI Kediri, 2025)
The problems addressed in this study are the students’ low confidence and performance in English speaking and comprehension due to uniform teaching strategies that do not accommodate diverse learning needs. Speak It, Love It, Ace It